PERAN ESTROGEN DAN PROGESTERON TERHADAP KANKER PAYUDARA - Suparman, Erna; Suparman, Eddy (UNIVERSITAS SAM RATULANGI, 2014)
Abstract: Sex steroid hormones estrogen and progesterone are the main compounds in hormone replacement therapy (HRT). Due to the Woman’s Health Initiative report 2002, the use of these compounds was controversial. It was reported that these hormones increased the risks of stroke, coronary heart disease, venous thromboembolism, and breast cancer, especially if they were used for a long period of time. The role of sex steroid hormones in inducing or promoting breast malignancy is still not clearly understood. Hypothetically, the polymorphism in receptors and steroidogenesis in breast tissues are involved in promoting the proliferation of breast cells that may trigger carcinogenesis. Although there is a significant benefit in administration of HRT for the menopausal women, there are also probable risks due to this therapy. After prolonged debates and controversies about HRT, it is accepted that there is a significant increase in breast cancers due to the use of combined HRT after 3-4 years. Due to the adverse outcome, the use of hormone therapy must start from the lowest dose and for the shortest period of time.Keywords: hormone replacement therapy, estrogen, progesterone, breast cancerAbstrak: Hormon seks steroid estrogen dan progesteron merupakan kandungan utama dari terapi sulih hormone (TSH). Penggunaan kedua hormon tersebut mendatangkan kontroversi setelah Woman’s Health Initiative pada tahun 2002 melaporkan peningkatan risiko stroke, penyakit jantung koroner, venous thromboembolism dan kanker payudara terutama pada penggunaan jangka panjang. Peran hormon steroid seks dalam meningkatkan keganasan payudara belum jelas dipahami. Secara hipotetik, polimorfisme pada reseptor dan kemampuan steroidogenesis dari jaringan payudara berperan dalam meningkatkan proliferasi sel-sel payudara dan memicu karsinogenesis. Meskipun terdapat keuntungan bermakna dari penggunaan TSH pada wanita menopause, namun terdapat juga kemungkinan risiko yang perlu dipertimbangkan. Setelah melalui berbagai perdebatan dan kontroversi mengenai TSH, disepakati bahwa terdapat peningkatan bermakna dari keganasan payudara setelah 3-4 tahun menggunakan TSH kombinasi. Oleh karena efek samping tersebut maka penggunaan TSH harus dimulai dengan dosis yang serendah mungkin dengan durasi pemakaian yang sesingkat-singkatnya.Kata kunci: terapi sulih hormon, estrogen, progesteron, kanker payudara